Tropical cyclogenesis induced by ITCZ breakdown in association with synoptic wave train over the western North Pacific. (27th July 2013) - Cao, Xi; Chen, Guanghua; Chen, Wen
Abstract: Compared to the eastern Pacific and eastern Atlantic, tropical cyclogenesis associated with breakdown of the intertropical convergence zone (ITCZ) was less documented over the western North Pacific (WNP). A typical case in boreal summer 2006 over the WNP, in which tropical cyclogenesis is induced by ITCZ breakdown in association with synoptic‐scale wave train (SWT), is examined through observation analysis and numerical simulations. Observational analysis displays that a northwest–southeast‐oriented SWT developed and propagated northwestward several days prior to ITCZ breakdown. Furthermore, the comparisons of simulation results reveal the role of the SWT in ITCZ breakdown. On one hand, the SWT within the ITCZ region is conducive to break down the ITCZ by enhancing the potential vorticity (PV), strengthening the meridional PV gradient and producing an evident sign reversal of PV gradient. On the other hand, the anomalous anticyclonic circulation related to the SWT north of ITCZ can reduce the meridional scale of PV band and thus increase the meridional PV gradient to accelerate ITCZ breakdown .